Diseño y construcción de un sistema automático de pesaje y control estadístico mediante básculas electrónicas inteligentes. - Armijos Cabrera, Nilson De Jesús (2008)
In this paper extensive information on weighing systems is collected and statistical control to make it possible to carry out the construction in our midst. the process of developing a sequential manner and the specific devices that can fulfill the roles planteadas.Se perform the design and construction of an electronic card that allows the built system can operate in a unified manner, or presented the entire assembly is connected at a time, and not have to make connections or disconnections preventing repetitive contacts may fail, facilitating the PLC is governing the functions designed on the card, making are met according to the project developed. For the design of the mechanisms and the contribution of electronic devices with the mechanical part it was taken on the experiences made by the authors of different projects where good technical advice was obtained and should take into account such important aspects as the proper assembly the whole structure, as well as protection relays and auxiliary double protection and comprehensive security of all equipment and accurate for sizing machine installation and general recommendations.